Analysis of genetic diversity among Iranian populations of Ficus carica L. (Moraceae) - Zolfaghari, M.R.; Salimpour, F.; Sharifnia, F.; Marandi, S.J. (Acta Biologica Sibirica, 2019)
Ficus carica L. is a species of Moraceae family that has been cultivated in different parts of the world from ancient time. Its fruit is eaten by human and has several medicinal properties. This species widely grows and cultivated in various parts of Iran. For this, in the current study, we investigated infraspecific genetic variation and population structure of F. carica in the country. 14 natural populations of F. carica were collected and their genomic DNA were extracted and tested with RAPD molecular technique. Parameters of population’s genetic diversity varied among the studied populations. In addition, AMOVA test revealed significant variations among the populations. The studied populations clustered separately in UPGMA tree of RAPD data, moreover PCA and MDS plots produced similar results. STRUCTURE analysis revealed the best number of k = 9. Based on Nei’s genetic distance, we had nine distinct groups. Genetic clustering patterns according to UPGMA trees of RAPD data and Nei’s genetic distance were more similar with the results of STRUCTURE analysis. The small amount of Nm) the product of the effective size of individual populations (N) and the rate of migration among them (m) (value showed limited gene flow among the studied populations, therefore it seems that high genetic variations among these populations may be related less or few amount of gene exchange among populations.